Effectiveness of concentrated growth factors with or without grafting materials in maxillary sinus augmentation: a systematic review - Omar A. Al-Aroomi; Yanjing Ou; Karim A. Sakran; Huachen Chen; Yuxuan Lin; Yan Gao; Qin Cai; Jiang Chen (BMC Oral Health, 2024)
Abstract Concentrated Growth Factor (CGF) is a highly effective biomaterial known for its ability to promote tissue regeneration. While it’s been studied extensively in intraoral procedures and bone grafting, its benefits in maxillary sinus lifting lack substantial evidence. This review aimed to evaluate CGF’s effectiveness in maxillary sinus augmentation, focusing on clinical, radiographic, and histological outcomes. A comprehensive literature search was conducted across PubMed, Scopus, Web of Science, Google Scholar, and Cochrane Library databases using specific mesh terms and keywords and adhered to PRISMA guidelines. Studies up to March 2024 involving transcrestal or lateral maxillary sinus floor elevation with CGF, either alone or in combination with grafting materials, were included. Out of 783 publications, 13 studies met the eligibility criteria. The review assessed CGF’s role in minimizing postoperative complications, enhancing new bone formation, and improving implant survival. Despite data variability among studies, the majority reported that CGF positively influenced maxillary sinus augmentation outcomes. While more robust randomized clinical trials are required to draw definitive conclusions, initial results are promising, and the findings suggest that CGF utilization in maxillary sinus augmentation seems to enhance clinical outcomes by promoting vascularization and regeneration at the surgical sites and improving both the quality and quantity of newly formed sinus bone. Furthermore, it exhibits potential for improving postoperative sequelae and achieving high implant survival rates.